Some Basic Properties of Certain New Subclass of Meromorphic Functions - Lei Shi; Zhi-Gang Wang (Journal of Function Spaces)
We introduce and investigate a new subclass ℳ(β,η) of meromorphic functions. Some interesting properties such as inclusion relationship, coefficient estimates, neighborhoods, and partial sums are proved. Connections of the results with known results are also considered.